Form for reporting Iowa Christmas bird counts to Iowa Bird Life, Dean Mosman, January 2, 1989 - Mosman, Deanet al (1989)
Iowa Christmas bird counts of species found in Alleman contributed by Dean Mosman, January 2, 1989. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of winter 1988-1989. Epson - sheet feed